BAY 81‐8973 safety and efficacy for prophylaxis and treatment of bleeds in previously treated children with severe haemophilia A: results of the LEOPOLD Kids Trial. (9th December 2015) - Ljung, R.; Kenet, G.; Mancuso, M. E.; Kaleva, V.; Rusen, L.; Tseneklidou‐Stoeter, D.; Michaels, L. A.; Shah, A.; Hong, W.; Maas Enriquez, M.; ,
Abstract : Introduction: BAY 81‐8973, a full‐length, unmodified, recombinant factor VIII (FVIII) in development for treatment of haemophilia A, has the same primary amino acid sequence as Bayer's sucrose‐formulated recombinant FVIII but is produced with more advanced manufacturing technologies. Aim: To demonstrate safety and efficacy of BAY 81‐8973 for prophylaxis and treatment of bleeds in previously treated children. Methods: In this phase III, multicentre, open‐label, nonrandomized study, boys aged ≤12 years with severe haemophilia A and ≥50 exposure days (EDs) to FVIII products received prophylaxis with BAY 81‐8973 25–50 IU kg −1 ≥2 times weekly for ≥50 EDs. The efficacy endpoint was annualized number of total bleeds. Adverse events (AEs) and immunogenicity were assessed. Results: Fifty‐one patients were treated (age: <6 years, n = 25; 6–<12 years, n = 26) with a 2× per week (43%) or >2× per week (57%) regimen at study start. Median [quartile 1; quartile 3 (Q1; Q3)] annualized number of bleeds for the combined age groups was 1.90 (0; 6.02) for total bleeds, 0 (0; 2.01) for joint bleeds and 0 (0; 0) for spontaneous bleeds. Median (Q1; Q3) annualized number of total bleeds within 48 h of previous prophylaxis infusion was 1.88 (0; 3.97) for children aged <6 years and 0 (0; 1.96) for children aged 6–<12 years. No drug‐related serious AEs or inhibitors were reported. Conclusions: Prophylaxis with BAY 81‐8973 using individualized prophylaxis regimens of 2× per week, 3× per week and every‐other‐day infusions was efficacious in prevention and treatment of bleeds in children with severe haemophilia A. Treatment with BAY 81‐8973 was well tolerated.